2012
DOI: 10.1097/jom.0b013e3182572e53
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Obesity Measures and Selected Comorbidities in Former National Football League Professional Athletes

Abstract: Percent body fat measured by dual energy x-ray absorptiometry provides a more accurate measure of obesity than does BMI among retired football players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…it was shown that body fat percentage provides a more accurate evaluation of obesity than what BMI does among retired football players. [ 3 ] Moreover, the effect of genetic difference between study groups on the result of weight and body fat percentage cannot be disregarded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…it was shown that body fat percentage provides a more accurate evaluation of obesity than what BMI does among retired football players. [ 3 ] Moreover, the effect of genetic difference between study groups on the result of weight and body fat percentage cannot be disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Obesity is associated with several problems, including cardiovascular diseases, diabetes, high blood pressure, and other metabolic disorders. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Using BMI to determine obesity could have overestimated its prevalence in the retired NFL players if they had greater muscle mass relative to the general population. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Multivariable models were adjusted for age, height and weight. Body mass index is a potentially limited metric in athletic populations and was not used 23, 24…”
Section: Methodsmentioning
confidence: 99%